2018
DOI: 10.1371/journal.pone.0205243
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive behavioral therapy a better choice for women with postnatal depression? A systematic review and meta-analysis

Abstract: The present study evaluated the combined effectiveness of cognitive behavioral therapy (CBT) for postnatal depression. A systematic search was conducted across databases including PubMed, Embase, and the Cochrane library to identify the randomized controlled trials (RCTs) that assessing CBT versus control for postnatal depression until March 2017. Data was extracted by two reviewers, independently. The Review Manager 5.3 and Stata 11.0 were used to calculate the synthesized effect of CBT on depression, and anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…Psychological treatments are part of the management of all depressions, and, because they do not expose the developing foetus or nursling to medications, should be offered to all women with a perinatal depression. In the case of postnatal depression, a recent systematic review and meta-analysis concluded that CBT monotherapy is sufficient to improve symptoms and quality of life in postnatal depression (Huang et al, 2018), consistent with an early systematic review of intervention in primary care settings (Stephens et al, 2016). In both reviews, benefits were both immediate and maintained in the medium term.…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 56%
“…Psychological treatments are part of the management of all depressions, and, because they do not expose the developing foetus or nursling to medications, should be offered to all women with a perinatal depression. In the case of postnatal depression, a recent systematic review and meta-analysis concluded that CBT monotherapy is sufficient to improve symptoms and quality of life in postnatal depression (Huang et al, 2018), consistent with an early systematic review of intervention in primary care settings (Stephens et al, 2016). In both reviews, benefits were both immediate and maintained in the medium term.…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 56%
“…Cognitive Behavioral Therapy is a short‐term, structured, evidence‐based psychotherapy that aims to change patterns of thinking and behavior that contribute to the development and persistence of mental health problems like depression and anxiety. When used to treat PPD, CBT is as effective as individual CBT, and may be more effective than standard care (i.e., antidepressant medication and counseling from a GP) (Cuijpers et al., 2013; Huang, Zhao, Qiang, & Fan, 2018; Sockol, Epperson, & Barber, Jacques, 2011). Because CBT is easily manualized and can be delivered by professionals from a wide range of professional backgrounds and experience (Bieling, McCabe, & Antony, 2009), it was thought to be ideal for delivery by PHNs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of CBT are understudied. CBT’s previous research on perinatal depression and on effectiveness of psychotherapy for non-perinatal adult PD by the rigid systematic review has important implications for perinatal PD [2, 16]. The recent review by meta-analysis including 20 RCTs, including 3623 women, show that CBT as psychotherapy significant improved depression symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
“…CBT’s previous research on perinatal depression and on effectiveness of psychotherapy for non-perinatal adult PD by the rigid systematic review has important implications for perinatal PD [2, 16]. The recent review by meta-analysis including 20 RCTs, including 3623 women, show that CBT as psychotherapy significant improved depression symptoms [16]. In addition, the review suggested that the intervention group had a lot of cured women than the control group that treatment as usual at almost of RCTs: Short term Odds Ratio: 6.57; Long term Odds Ratio: 2.00).…”
Section: Introductionmentioning
confidence: 99%